Whether Economic Policy Uncertainty Instigates an Increase in The Cash Holdings of Singaporean-Listed Firms? - Thi Huong Giang Vuong,; Huu Manh Nguyen,; Wing-Keung Wong, (Asian Academy of Management Journal of Accounting and Finance, 2023)
Our paper investigates how economic policy uncertainty (EPU) affects Singaporean-listed firms’ corporate cash holdings after the global financial crisis. We apply various technical analyses for panel models of 4,253 yearly observations. Our results indicate that the Singaporean-listed firms’ cash holdings ratio (CHR) decreases when Singapore’s EPU increases in the period 2009–2018. Further, either global EPU or U.S. EPU indicators are correlated negatively with Singaporean-listed firms’ cash reserves. The corporate managers’ precautionary motive was not urged by the rise of EPU in the Singapore market. On the other hand, our empirical evidence suggests that Singapore’s corporate managers have an explicit speculative incentive in the context of the increased EPU in the post-financial crisis period. This research provides evidence that is at odds with the corporate managers’ classical view on precautionary cash savings in the context of the increased uncertainty of economic policy.